Uji Standarisasi Parameter Spesifik dan Nonspesifik serta Penetapan Kadar Total Fenolik Ekstrak Daun Kelor (Moringa Oleifera) - Rahmiyati Hi Samang; Fahmi Sadik; Ismail Rahman (Syntax Corporation Indonesia, 2025)
This study aims to standardize specific and non-specific parameters and determine the total phenolic levels in moringa leaf extract (Moringa oleifera) taken from Ternate. The standardization of specific parameters includes organoleptic, ethanol soluble juice content, and watersoluble juice content, while nonspecific parameters include drying shrinkage, moisture content, and ash content. The determination of total phenolic levels was carried out using the Folin-Ciocalteu method. The results of the study showed that moringa leaf extract met the requirements of standardization of specific and non-specific parameters according to the Indonesia Herbal Pharmacopoeia. The total phenolic content was expressed in Gallic Acid Equivalent (GAE) units of 206.36 mg GAE/g sample. This study shows that moringa leaf extract has good quality and safety in accordance with pharmaceutical standards.